Improvement of High Strength Automotive Steels Wettability Properties Using CO2 Laser Surface Treatment - Tajti, Ferenc; Berczeli , Miklós; Weltsh, Zoltán (International Journal of Engineering and Management Sciences, 2019)
As a result of stricter environmental and safety standards, vehicle manufacturers have to reduce the weight of the vehicles, because 10% weight loss cause 8-10% reduction of fuel consumption. To reduce car’s weight and increase safety, vehicle manufacturers use high-strength steels. Further weight reduction can be achieved by using corresponding bonding technology (soldering, sticking) and optimizing these technologies can increase the strength of the joints. According to literature research, the improvement of interface properties has a large effect on bonding technologies. In order to improve interface properties, we can use multiple surface treatments. In our research we investigate the effects of CO2 laser surface treatment on high strength steels, because CO2 lasers are often used in the vehicle industry. In order to detect the effect of surface treatment, we investigate the wettability of the treated and untreated steels. In our research we measure the surface tension of treated and untreated steels. Our main goal is to improve wettability properties thus the bonding technology. In our research we used DP 600 high strength steel sheet with the thickness of 1 mm. We cut the steel sheet to 25mm wide and 55mm long workpieces. Before the surface treatment, the workpieces had to be cleaned and degreased using methanol. We searched for parameters that do not cause any visible changes on the surfaces. Among the parameters of the treatment we were able to change the output power of the laser. We used contact angle measurement to examine the wettability.